Does trade freedom affect exchange rate movement? a perspective of high-technology trade - Cong, Shufeng; Chin, Lee; Kumarusamy, Risidaxshinni (Routledge, 2024)
Changes in the degree of trade freedom influence economic development and foreign investment, which in turn, affect currency values and exchange rate movements. Therefore, this study examined the direct and indirect impacts of trade freedom on exchange rate movement in emerging, developing, and developed economies. Empirical tests conducted using panel data from 75 countries revealed that trade freedom has a nonlinear U-shaped relationship with exchange rate movement, which is positively moderated by high-technology trade and foreign direct investment. Additionally, the results of heterogeneity analysis showed that trade freedom has a linear positive impact on the exchange rate movement of developed economies but a U-shaped impact on emerging and developing economies, with a stronger impact on emerging economies. The findings of this study provide valuable insights for governments to strike a balance between promoting trade freedom and maintaining currency exchange rate stability.